A new gene set identifies senescent cells and predicts senescence-associated pathways across tissues - Saul, Dominik (Dryad, 2022)
Although cellular senescence drives multiple age-related co-morbidities
through the senescence-associated secretory phenotype (SASP), in vivo
senescent cell identification remains challenging. Here, we generated a
gene set (SenMayo) and validated its enrichment in bone biopsies from two
aged human cohorts. We further demonstrated reductions in SenMayo in bone
following genetic clearance of senescent cells in mice and in adipose
tissue from humans following pharmacological senescent cell clearance. We
next used SenMayo to identify senescent hematopoietic or mesenchymal cells
at the single cell level from human and murine bone marrow/bone scRNA-seq
data. Thus, SenMayo identifies senescent cells across tissues and species
with high fidelity. Using this senescence panel, we were able to
characterize senescent cells at the single-cell level and identify key
intercellular signaling pathways. SenMayo also represents a potentially
clinically applicable panel for monitoring senescent cell burden with
aging and other conditions as well as in studies of senolytic drugs.
Source Code Raw counts
Keywords: FOS: Medical and health sciences